The Origins of the Impediment of Consanguinity in the Direct Line and in the Second Degree in the Lateral Line - DZIERŻON, GINTER (Prawo Kanoniczne, 2012)
The author of the study presented a doctrinal discussion of the impediment of kinship in the direct line and in the second degree in the lateral line. The analysis carried out shows that in the modern doctrine the origin of the impediment of kinship is not obvious. Canonists do agree that the impediment of consanguinity in the direct line is derived from natural law. However, some doubts arise concerning the origin of impediment of kinship in other degrees in the direct line and in the second degree in the lateral line. The author believes that this doctrinal uncertainty comes form the fact that the Holy See twice sanctioned marriages contracted by half – brother and half – sister. G. Dzierżon’s focus of attention was also the issue of consanguinity in the context of in vitro fertilization. He pointed out that some cases do not fall under this impediment to marriage. Nonetheless, is such cases, he postulates introducing an impediment in Church Law for the same reasons which determined the legislation of the impediment of decency and legal kinship.